Plagiarism in ‘Evaluation of drug release kinetics from ibuprofen matrix tablets using HPMC' (J App Pharm Sci, 2011; 01 (06): 186-190) (Journal of Applied Pharmaceutical Science)
This is to inform the readers that article titled ‘Evaluation of drug release kinetics from ibuprofen matrix tablets using HPMC' has been retracted. It has come to the notice of editors of Journal of Applied Pharmaceutical Science that, this article contains lots of similarities to the article ‘Evaluation of drug release kinetics from Ibuprofen matrix tablets using HPMC’ by Shoaib et al., (2006). Thus, we retract this article from the literature according to the guidelines of Committee on Publication Ethics (Wager et al., 2009).